An examination of sex differences in associations between cord blood adipokines and childhood adiposity. Issue 3 (16th December 2019) - Ashley‐Martin, Jillian; Karaceper, Maria; Dodds, Linda; Arbuckle, Tye E.; Ettinger, Adrienne S.; Fraser, William D.; Muckle, Gina; Monnier, Patricia; Fisher, Mandy; Kuhle, Stefan
Summary: Background: Though the physiological roles of adipokines in metabolism, insulin resistance and satiety are clear, literature regarding associations between cord blood adipokine levels and childhood adiposity is equivocal. Objectives: To determine whether cord blood levels of leptin and adiponectin are associated with adiposity in children 2 to 5 years of age, and whether such associations are modified by sex. Methods: Leptin and adiponectin levels were measured in cord blood and anthropometric measures were completed on 550 children enrolled in the Maternal–Infant Research on Environmental Chemicals Child Development Plus study (MIREC‐CD Plus). We used multivariable linear and Poisson regression models to determine associations between cord blood adipokine levels and child body mass index (BMI), triceps and subscapular skinfold thickness and risk of overweight/obesity and to assess effect modification by child sex. Results: Cord blood adiponectin was significantly associated with modest increases in BMI and the sum of triceps and subscapular skinfold z‐scores in boys but not girls. A doubling of adiponectin levels was associated with a 30% increased risk of overweight/obesity in boys (RR = 1.30; 95% CI: 1.02, 1.64). Leptin was not associated with anthropometric measures in either sex. Conclusions: The observed associations between adiponectin and adiposity in boys were statistically significant, of moderate magnitude, and underscore the value of considering sex‐specific patterns.